Dynamics of Fundamental Factors and Macroeconomics in Determining The Stock Prices of Islamic Banks in Indonesia - Syauki, Ahmad; Anggraeni, Erike; Iqbal, Muhammad (UIN Siber Syekh Nurjati Cirebon, 2024)
This study aims to analyse the influence of fundamental variables of Islamic banks in Indonesia and Indonesian macroeconomic variables on the dynamics of Islamic bank stock prices in Indonesia in the period 2020 to 2023. This study uses a quantitative method with secondary data in the form of Islamic bank financial reports and publication data from Bank Indonesia. The analysis techniques used include descriptive statistics, classical assumption tests consisting of normality tests, multicollinearity tests, autocorrelation tests, and heteroscedasticity tests, as well as panel data regression techniques. The results of the study show that EPS has a positive but insignificant effect on stock prices, NPM has a negative but insignificant impact on stock prices, inflation has a negative but insignificant effect on stock prices, and interest rates have a positive but insignificant impact on stock prices. While together, all independent variables have a positive but insignificant impact on stock prices.